Changing rooms and changing rules: a trans teacher's lessons in gender and institutional ambiguity - Yau, Yi; Shen, Ya Chun; Lim, Boon Hooi (Frontiers in Sociology, 2025)
This study adopts a critical autoethnographic approach to explore how a transgender teacher navigates structural violence and institutional erasure during gender transition within Taiwan's educational system, addressing a research gap on transgender educators in Asia. Through embodied narratives of administrative encounters, spatial exclusion, sexual harassment, and pedagogical tensions, the research reveals a disconnect between gender diversity legislation and the institutional inertia of school governance. Drawing on “administrative violence,” “institutional diversity,” and “gender performativity,” it analyzes how everyday practices such as data fields, bathroom access, gendered evaluations, professional recognition, and harassment responses reproduce epistemic violence and marginalization. It further argues that non-normative embodiment, relational pedagogy, and affective labor serve as key strategies for reconfiguring teacher subjectivity and challenging dominant assumptions of a “qualified” educator. By highlighting the dual condition of visibility and vulnerability in classrooms, the research shows transgender teachers as not only victims but also agents of disruption and transformation.